Performance Test of Various Indonesian Natural Zeolites as Composite Components of NiMo/Al2O3-Zeolite Catalysts for Hydrocracking Used Cooking Oil into Biohydrocarbons - Kurniawan, Amar Ariza; Rustyawan, Wawan; Ibadurrohman, Muhammad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Due to increasing demand for alternative energy sources, nonedible used cooking oil is being converted into biohydrocarbons as an eco-friendly renewable option. This study explores the use of three Indonesian zeolites; Lampung, Bayah, and Tasikmalaya as a composite components of NiMo/Al2O3-Zeolite catalysts to enhance conversion and yields, promoting the use of sustainable domestic resources. The NiMo/γ-Al2O3-zeolite catalyst, with alumina-to-zeolite ratios of 75:25 and 25:75, effectively converted used cooking oil into biohydrocarbons products—green diesel and gasoline. The NiMo/γ-Al2O3 (75%)-Bayah Natural Zeolite (25%) catalyst exhibited a surface area of 194 m²/g, pore volume of 0.45 cm3/g, 7.01% Mo content, and a crystal size of 117.74 nm. At 370 °C, this catalyst achieved a 93% conversion, with GC-simdis analysis confirming 13% gasoline and 78% diesel fractions. This research demonstrates that Indonesian natural zeolites can be effectively used to convert used cooking oil into biohydrocarbons, achieving high conversion and desired product selectivity. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).